Nile river of gods [videorecording] - Cowling, Tim.; McKinnon, Michael; Olmert, Michael; Pye-Smith, Charlie ([S.l.] Discovery Production and McKinnon Films, 1994)
An exploration of time and space and life in the times of the Pharaohs and today. Discovers the natural beauty and spirituality of the people. Travels back in time to the scattered kingdoms of upper and lower Egypt. The ways and wildlife 3,000 years ago still survive.
Some conversations are in Arabic.
VHS.
Narrator, F. Murray Abraham ; editor, John Hackney.
Keywords: Nile river; Egypt -- Social life and customs; Ethiopia -- Social life and customs; Egypt -- Civilization; Egypt -- History; ASIAN HISTORY; GEOGRAPHY; SOCIOLOGY